Ethnic-Racial Relations and Music Teaching: considerations of ethnic knowledge in school practices (Orfeu, 2018)
This paper discusses the ethnic-racial education not only as a “content” of the curricular components, but mainly as a process of expansion for different epistemologies, cosmologies, for different possibilities of transmission and production of knowledge. This implies a revision of values and concepts, repositioning of hierarchies, modifications of spatial structures, among other aspects. From this perspective I present some reflections about my job as a primary school teacher in the arts-music discipline, at the same time in dialogue with the anthropological and ethnomusicological theories, areas that I studied in master and doctorate degree while was working in school. I discuss theoretical notions of “school as frontier” (TASSINARI, 2012), “appropriate dispositions” (INGOLD, 2000), “dancing ear” (OLIVEIRA, 2015), “musicalization of the other” (HILL, 2014) at the same time with the school experiences. With this, I try to problematize the school knowledge, the routines that do not allow the validation of other ways of learning, other ways of relating to and producing knowledge.
Keywords: school practices; ethnic-racial diversity; knowledge production